Implementasi Undang – undang Nomor 39 Tahun 2007 Tentang Cukai Terhadap Produk Hasil Pengolahan Tembakau Lainnya Berupa Liquid Personal Vaporizer yang tidak Dilengkapi oleh Pita Cukai - Widodo, Dimas Tragari Eldo; Bidasari, Anindya; Suciati, Suciati (Jurnal Panorama Hukum, 2021)
The background of this research is that the determination of Customs collection on Liquid Personal Vaporizer can be concluded that the government has found an answer to the debate that has been happening in Indonesia regarding the prohibition of Personal Vaporizer. As for the formulation of the problem in this research is How the Implementation of Ã¢â‚¬Å“Law No. 39 of 2007Ã¢â‚¬Â concerning Customs for other tobacco processing products in the form of Liquid Personal Vaporizer, How is the solution or legal remedy in the process of implementing Customs on other tobacco processed products in the form of Liquid Personal Vaporizer which is not equipped with Customs stamps. The type of research in this research is sociological juridical which in other words is a type of sociological legal research and can also be called field research, which examines the applicable legal provisions and what happens in reality in society. While the dataVanalysis technique uses a qualitative descriptive method. The conclusion obtained by the researchers from the results of this research is that although most of them are regulated by ministerial regulations, the application of Customs for HPTL products in the form of Liquid Personal Vaporizers is still based on Law No.39 of 2007 concerning Customs for all regulations related to the application of Customs. And also the legal settlement for Liquid Personal vaporizer that is not equipped with Customs stamps in the Malang Customs Customs KPPBC area using non-penal channels for the settlement.